Encouraging and Developing the Participative Bodies for a Synodal Church - Poothavelithara, Varghese (Asian Horizons, 2020)
An effective means to become a synodal Church is to encourage and develop the participative bodies at the different levels of the Church. The first level is that of particular churches (dioceses/eparchies). Vatican II with its new ecclesiological vision invited the Church to a participative style and proposed to establish structures of participation. The initiations done by the post-conciliar documents to concretize the conciliar invitation and proposals were completed by the new Codes—CIC and CCEO. They made obligatory the establishment of the presbyteral council, college of consultors, and finance councils and recommended the establishment of pastoral councils. Several documents of the Apostolic See also have made references to these canonical bodies. While the importance of these bodies is acknowledged on one side, the canonical discipline and the ecclesiastical teachings have simultaneously placed limitations in the involvement and participative nature of these bodies. Pope Francis invites the particular churches to encourage and develop these bodies to exercise synodality in them. It is an invitation to transform these bodies as forums of honest speaking and sincere listening. Within the parameters of the existing canonical discipline, this article tries to indicate some orientations for the achievement of this transformation.